2021
DOI: 10.1038/s41398-021-01491-8
|View full text |Cite
|
Sign up to set email alerts
|

Compassion toward others and self-compassion predict mental and physical well-being: a 5-year longitudinal study of 1090 community-dwelling adults across the lifespan

Abstract: There is growing interest in the role of compassion in promoting health and well-being, with cross-sectional data showing an inverse correlation with loneliness. This is the first longitudinal study examining both compassion toward others (CTO) and compassion toward self (CTS) as predictors of mental and physical health outcomes including loneliness, across adult lifespan. We followed 552 women and 538 men in San Diego County for up to 7.5 (mean 4.8 and SD 2.2) years, using validated rating scales for CTO, CTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 95 publications
0
22
1
Order By: Relevance
“…In modern times, the ability to care for others in need should confer the same benefits, but people can also engage in prosocial behaviors that help others at potential personal cost. The tendency to have compassion for others in need and compassionate rather than self-image goals has been associated with indices of better social connections, such as perceived social support [19] and less loneliness [20].…”
Section: Theories Of Compassionmentioning
confidence: 99%
“…In modern times, the ability to care for others in need should confer the same benefits, but people can also engage in prosocial behaviors that help others at potential personal cost. The tendency to have compassion for others in need and compassionate rather than self-image goals has been associated with indices of better social connections, such as perceived social support [19] and less loneliness [20].…”
Section: Theories Of Compassionmentioning
confidence: 99%
“…Our results further provide strong evidence on the link between self-compassion and gamma power as well as coherence. It remains an open question whether compassion for others and self-compassion are in fact part of the same overarching construct ( Anālayo & Dhammadinnā, 2021 ; Lee et al, 2021 ; MacBeth & Gumley, 2012 ). While some studies indicate compassion to be synonymous with self-compassion in mental health ( MacBeth & Gumley, 2012 ), others found no relationship between self-compassion and compassion for others ( López et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…So, we must understand this data in the context of Spain's initial COVID-19 lockdown. Nevertheless, Lee et al (2021) already found that compassion toward others and selfcompassion were associated with better mental well-being across the adult lifespan, so it could be hypothesized that self-compassion might play an important role to buffer the adverse mental health impacts of COVID-19 in the future and in prolonged periods of lockdown (Lau et al 2020).…”
Section: Discussionmentioning
confidence: 99%